Integrating Agricultural Science and Community Knowledge through Service-Learning to Enhance Food Security: A Participatory Lens - Glen Legodu; Benjamin Seleke (Journal of Education and Learning Technology)
Food security is a growing concern on the African continent. Creative ways are required to maximise the quantity and quality of food production in society to meet the needs of the community and learners that form part of the increasing population. As an approach, service-learning can potentially merge academic learning with community engagement to address food security issues. However, when community wisdom is disregarded as equal to formal education, significant information may be omitted, hindering all stakeholders’ deep learning. This paper aimed to create a service-learning experience that allows learners and the community to learn agricultural science and practice sustainably to address food security. Data was generated in four cycles of a participatory action research design, using vegetable garden and livestock management strategies. The thematic analysis indicated that the process gave 10 participants a better understanding of managing vegetable gardens and livestock farming sustainably. The participants valued Western knowledge without neglecting the local wisdom perspectives shared throughout the process. This reciprocal learning boosted development on personal and professional levels. The study proposes that food security cannot be effectively addressed by favoring one dominant knowledge system. Instead, blending local wisdom and Western perspectives, when applied with care, could eradicate poverty and hunger and promote sustainable food production in Africa.